2017
DOI: 10.1002/pon.4492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stepped psychooncological care on referral to psychosocial services and emotional well‐being in cancer patients: A cluster‐randomized phase III trial

Abstract: Objective: Emotional distress in cancer patients often goes unnoticed in daily routine; therefore, distress screening is now recommended in many national guidelines. However, screening alone does not necessarily translate into better well-being. We examined whether stepped psychooncological care improves referral to consultation-liaison (CL) services and improves well-being.Methods: In a cluster-randomized trial, wards were randomly allocated to stepped versus standard care. Stepped care comprised screening fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Nevertheless, many patients with pathological anxiety in the medical setting remain undetected . Given the availability of effective treatment methods, screening for anxiety disorders in oncological settings seems warranted: Although a recent randomized controlled trial on screening for emotional distress among cancer patients did not find a direct improvement in well‐being, screening led to improved referral to psychiatric/psychological care …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many patients with pathological anxiety in the medical setting remain undetected . Given the availability of effective treatment methods, screening for anxiety disorders in oncological settings seems warranted: Although a recent randomized controlled trial on screening for emotional distress among cancer patients did not find a direct improvement in well‐being, screening led to improved referral to psychiatric/psychological care …”
Section: Introductionmentioning
confidence: 99%
“…4 Given the availability of effective treatment methods, 5 screening for anxiety disorders in oncological settings seems warranted: Although a recent randomized controlled trial on screening for emotional distress among cancer patients did not find a direct improvement in well-being, screening led to improved referral to psychiatric/psychological care. 6 Within the anxiety disorders, generalized anxiety disorder (GAD) may be of special interest. The risk of GAD may be heightened after a severe life stressor such as cancer, 2…”
Section: Introductionmentioning
confidence: 99%
“…20 So far, we know that patient-oncologist communication during the distress screening process might be positively linked to patients' uptake behaviour and lead to more adequate referral to POS. 8,21 Singer and colleagues 22 found that a stepped care model in which patients and oncologists discussed distress screening results decreased referrals in patients without psychiatric comorbidities and increased referrals in patients with psychiatric comorbidities compared with the standard care model without a discussion. Some studies have suggested that informing patients about the availability and benefits of psychological support and providing them with practical information about psycho-oncological treatment may increase uptake of services.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this is a monocentre observational study conducted at a Swiss comprehensive cancer centre, with cultural particularities regarding the strong position of the oncologist in the coordination of psychosocial care 31. Hence, our centre might not represent other outpatient oncological settings that integrate POS into a stepped-care model where the treating oncologist generally addresses psychosocial issues 22. However, our sample included a large gender-balanced sample of cancer patients, a broad array of cancer types, and the POS uptake rate was comparable to other outpatient oncological settings 11.…”
mentioning
confidence: 99%
“…Stepped care models have been recommended as a way to improve access and deliver care efficiently and have been successfully implemented in psychosocial care for cancer patients . Our findings demonstrate that stepped care is effective for insomnia in cancer survivors and that a sizable proportion of cancer survivors suffering from insomnia experience meaningful symptom improvement from a low‐intensity sleep hygiene education session.…”
Section: Discussionmentioning
confidence: 66%